The case of primary fallopian tube carcinoma - Kołodziejczyk-Melon, Agata; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2013)
Primary cancer of the fallopian tube is the least frequent female genital cancer. The incidence is estimated to be 1-2% of all genital cancers. The risk factors include infertility and chronic genital inflammation. Symptoms of the fallopian tube cancer are not specific enough. These include: colicky abdominal pain, abnormal vaginal/genital bleeding, and the presence of a tumor in the abdomen or pelvis. In the advanced stage, pain in the sacrum, feeling the urge to urinate, and ascites occur. A typical macroscopic image of limited fallopian tube cancer is a widened fallopian tube resembling a hydrocele or tubo-ovarian abscess. In the cross-section of the fallopian tube, a solid or pendula mass may be visible. Primary fallopian tube cancer is usually detected during the diagnosis of benign genital lesions or based on the results of the histopathological examination of material taken from patients operated on because of ovarian cancer. The authors present a case of primary fallopian tube carcinoma in a 41-year-old patient diagnosed because of abnormal uterine bleeding and pain in the lower abdomen. After a series of laboratory and imaging tests, the patient underwent laparoscopic hysterectomy (TLH) due to uterine myoma and resection of the right fallopian tube. Only when the final result of the histopathological examination of the removed fallopian tube was obtained (Carcinoma male differentiatum oviducti dextri), it was decided to expand the operation to remove appendages, omentum, vermiform appendage and pelvic lymph nodes. The presented case confirms that no specific symptoms of this cancer makes the diagnosis rather difficult.